Affect and groups - Mannix, Elizabeth A., 1960-; Neale, Margaret Ann; Anderson, Cameron P. (Emerald, 2007)
Affective phenomena permeate group life. When individuals work together in groups, feelings of pride, fear, hope, anger, and anxiety constantly emerge and have a profound influence on group member behavior. The experience and expression of moods and emotions shape whether group members form close bonds with one another, how they negotiate roles and status differences, resolve their conflicts, make decisions, and ultimately whether they accomplish their collective goals. After a long history of focusing on cognitive and behavioral processes, group researchers are beginning to take more seriously the role of affective phenomena. This tenth volume of Research on Managing Groups and Teams brings together some of the top researchers studying the interplay of groups and affect. The works presented examine how groups influence individual members emotional experiences; in turn, how a groups success depends on the emotions and emotional capabilities of its members; how moods and emotions mediate the effects of demographic diversity in groups, the emergence of intra-group conflict, and the attachment individuals feel to their groups; and, how emotions foster divisions between groups, organizations, or even societies. This book is of interest to anyone seeking to better understand group dynamics, the social nature of moods and emotions, or the ways in which affective phenomena can be leveraged to increase human performance and productivity. This book series is available electronically at website.
Keywords: Affect (Psychology); Social groups.; elektronické knihy; electronic books